Environmental health and hazard risk assessment : principles and calculations - Theodore, Louis (CRC Press, 2012)
"With the rise and expansion of the chemical and petroleum industries, so has there been a rise and expansion in related human health problems as well as human, material, and property losses due to fires, explosions, hazardous and toxic spills, equipment failures, and other accidents. This much-needed overview examines the fundamentals of health, safety, and accident management. It draws parallels between theoretical and real-world environmental problems as they relate to both human and environmental risk and offers in-depth guidance on human chemical exposure, emergency preparedness and response, environmental regulations, and much more"--